2004
DOI: 10.1007/s00421-004-1042-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 20-s and 180-s double poling interval training in cross-country skiers

Abstract: The purpose of this study was to investigate the effect of upper body 20-s or 180-s interval training, using a double poling ergometer, on upper body power output and selected physiological and biomechanical parameters in cross-country skiers. Twenty (12 male, 8 female) well-trained cross-country skiers took part. Two intervention groups, a 20-s interval training group (IT20; n=6) and a 180-s interval training group (IT180; n=7), underwent training three times a week for 6 weeks on a double poling ergometer. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 21 publications
10
47
3
4
Order By: Relevance
“…Both UBP 10 and UBP 60 correlated highly with UBP PEAK (r = 0.97 and 0.98, respectively, for absolute measures, and r = 0.93 and 0.95, respectively, for relative measures) for the entire group of 15 subjects. This supports earlier suggestions that a short sprint-type test of UBP may be a predictor of longer, more sustainable UBP (Heil et al 2004;Nilsson et al 2004;Stoggl et al 2006Stoggl et al , 2007a. For example, maximal strength training studies have suggested that an increased rate of force production during double poling may result in improved economy and an increase in time to exhaustion while double poling on an ergometer (HoV et al , 1999Osteras et al 2002).…”
Section: Long Versus Short Tests Of Upper Body Powersupporting
confidence: 67%
See 1 more Smart Citation
“…Both UBP 10 and UBP 60 correlated highly with UBP PEAK (r = 0.97 and 0.98, respectively, for absolute measures, and r = 0.93 and 0.95, respectively, for relative measures) for the entire group of 15 subjects. This supports earlier suggestions that a short sprint-type test of UBP may be a predictor of longer, more sustainable UBP (Heil et al 2004;Nilsson et al 2004;Stoggl et al 2006Stoggl et al , 2007a. For example, maximal strength training studies have suggested that an increased rate of force production during double poling may result in improved economy and an increase in time to exhaustion while double poling on an ergometer (HoV et al , 1999Osteras et al 2002).…”
Section: Long Versus Short Tests Of Upper Body Powersupporting
confidence: 67%
“…A modiWed Concept 2 rowing ergometer (Concept 2 Model D, Morrisville, VT, USA), similar to that described by Nilsson et al (2004), was used for all UBP testing in this study. In place of the sliding seat on a typical Concept 2 ergometer, a resistance-loaded trolley was connected to the chain that turned the air-braked Xywheel.…”
Section: Upper Body Power Ergometermentioning
confidence: 99%
“…Vesterinen et al [7] found that high-anaerobic capacity was linked to good performance in the first heats of sprint competition. In a study on anaerobic power in well-trained cross-country skiers, Nillson et al [19] showed that 6 week of upper-body interval training, 3 times a week, significantly increases maximum anaerobic power and minimum anaerobic power. Our results suggest that the aerobic high-intensity interval training with roller-ski promote increases in anaerobic capacity in cross-country skiers.…”
Section: Discussionmentioning
confidence: 99%
“…Vesterinen et al [2009] [23], found that high-anaerobic capacity was linked to good performance in the first heats of sprint competition. In a study on anaerobic power in well-trained cross-country skiers, Nillson et al [2004] [24], showed that 6 week of upper-body interval training, 3 times a week, significantly increases maximum anaerobic power and minimum anaerobic power. Our results suggest that the aerobic high-intensity interval training with rollerski promote increases in anaerobic capacity in cross-country skiers.…”
Section: Discussionmentioning
confidence: 99%